2023
DOI: 10.1038/s41598-023-33360-3
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological assessment of Phormidium sp. derived copper oxide nanoparticles for its biomedical and environmental applications

Abstract: Driven by the need to biosynthesized alternate biomedical agents to prevent and treat infection, copper oxide nanoparticles (CuONPs) have surfaced as a promising avenue. Cyanobacteria-derived synthesis of CuONPs is of substantive interest as it offers an eco-friendly, cost-effective, and biocompatible route. In the present study biosynthesized CuONPs were characterized and investigated regarding their toxicity. Morphological analysis using TEM, SEM and AFM showed the spherical particle size of 20.7 nm with 96%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Furthermore, It is postulated that there is an advanced link between the oxidative stress, genotoxicity and apoptosis (Shafagh et al, 2015). In addition, Asif et al (2023) reported the potential antioxidant activity of CuO NPs by 2, 2′ -azino-bis 3-ethyl benzthiazoline-6sulfonic acid (ABTS), 2,2′-diphenyl-1picrylhydrazyl (DPPH), hydrogen peroxide (H2O2) and superoxide radical (SOR) scavenging assays. Subsequently, the hepatocytes developed many adverse biological processes as cleavage of caspase-3, DNA fragmentation, breakdown of the cytoskeletal and nuclear protein, and formation of the granzymes (Martinvalet et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, It is postulated that there is an advanced link between the oxidative stress, genotoxicity and apoptosis (Shafagh et al, 2015). In addition, Asif et al (2023) reported the potential antioxidant activity of CuO NPs by 2, 2′ -azino-bis 3-ethyl benzthiazoline-6sulfonic acid (ABTS), 2,2′-diphenyl-1picrylhydrazyl (DPPH), hydrogen peroxide (H2O2) and superoxide radical (SOR) scavenging assays. Subsequently, the hepatocytes developed many adverse biological processes as cleavage of caspase-3, DNA fragmentation, breakdown of the cytoskeletal and nuclear protein, and formation of the granzymes (Martinvalet et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation inhibition index >IC50 was considered the maximum toxicity level of the metal taken in the study [89,90].…”
Section: Growing Environment and Experimental Metal Varinates Cu 2+ (...mentioning
confidence: 99%
“…At all concentrations, it was found that ascorbic acid and CfBio-CuONPs had signi cantly varying scavenging activities (p < 0.001). According to the studies of other professionals, copper oxide nanoparticles have a comparable pattern of antioxidant activity against DPPH (Dolati et al 2023;Asif et al 2023) In vitro toxicity assessment of CfBio-CuONPs…”
Section: Tem Imagingmentioning
confidence: 99%